Analysis of the Influence of Critical Thinking Ability on students Elementary School with a Problem Based Learning Model - Sri Nurjanah; Asrori Asrori; Hairida Hairida (Journal of Education Technology Information Social Sciences and Health, 2024)
This article aims to instill the influence of the Problem Based Learning model on elementary school students' critical thinking abilities. Using the literature study method, this research looks for theoretical references related to the cases or problems identified. The results show that Problem Based Learning improves critical thinking skills, because this educational strategy focuses on real-world challenges. Students must engage with these issues beyond mere understanding but also collaborate in resolving them, thereby effectively stimulating their abilities and skills, especially in critical thinking.